Decent work and informal employment: the case of Bulawayo Metropolitan Province (Central Business District) Zimbabwe - Bob, Shaka Keny (Rhodes University, Faculty of Humanities, Institute of Social and Economic Research, 2020)
Zimbabwe, similar to other developing countries experiences a high level of informal employment. However, most informal jobs are situated in very poor working conditions and are characterised by decent work deficits. Despite the fact that various studies have shown the importance of the informal economy in that it provides livelihood earning opportunities for the majority of people in the Global South, it has remained a largely forgotten sector in policy making in most countries. It is, therefore, important that informal work be taken seriously and efforts must be made to improve working conditions for the urban working poor in the developing world. The purpose of this study is to investigate on the self-reported experiences of informal workers to understand their perspectives surrounding the concept of decent work in the Zimbabwean context. The case study is the Bulawayo metropolitan province, and this study targeted informal workers who trade within the central business district. The study also aimed to measure the decent work deficit scores between two economic sectors (food and clothing traders). This was done by testing the suitability of the Edward Webster Decent Work Deficit Index as a methodology of measuring decent work at a micro level. The analysis is based on a mixed methods study which was carried out through the use of a semi-structured survey. The study revealed that decent work for the sampled informal workers meant work related improvements, insurances and risk management, right of expression and business advancement skills which closely resembles the International Labour Organisation's conceptualisation of decent work. The study also highlighted that childcare assistance and disability insurance are concepts which remained excluded in the current conceptualisation of decent work. The thesis offers a new policy angle which shows that to promote decent work the concept of heterogeneity must be adopted because inequalities persist within the informal economy. The study also suggested that the Edward Webster Decent Work Deficit Index can be used as an appropriate methodology of monitoring the progress towards achieving decent work at the micro level i.e. industry or individual level. This is because since the formation of the decent work concept; the International Labour Organisation has only provided a methodology of how to measure the progress of decent work at the county level. The survey findings revealed that food vendors scored more poorly on the decent work deficit index compared to the clothing traders. The study also identified that food vendors and clothing traders are faced with different challenges which suggests that policy makers must take that into consideration when attempting to design policies or programmes which are aimed at assisting informal workers.
Keywords: Labor -- Zimbabwe; Informal sector (Economics) -- Zimbabwe; Job creation -- Zimbabwe; Poor -- Zimbabwe -- Employment; Labor policy -- Zimbabwe; Football coaches -- South Africa